Loss of α(2)δ-1 Calcium Channel Subunit Function Increases the Susceptibility for Diabetes - Mastrolia, Vincenzo (Diabetes, 2017)
Reduced pancreatic β-cell function or mass is the critical problem in developing diabetes. Insulin release from β-cells depends on Ca(2+) influx through high voltage– gated Ca(2+) channels (HVCCs). Ca(2+) influx also regulates insulin synthesis and insulin granule priming and contributes to β-cell electrical activity. The HVCCs are multisubunit protein complexes composed of a pore-forming α1 and auxiliary β and α(2)δ subunits. α(2)δ is a key regulator of membrane incorporation and function of HVCCs. Here we show that genetic deletion of α(2)δ-1, the dominant α(2)δ subunit in pancreatic islets, results in glucose intolerance and diabetes without affecting insulin sensitivity. Lack of the α(2)δ-1 subunit reduces the Ca(2+) currents through all HVCC isoforms expressed in β-cells equally in male and female mice. The reduced Ca(2+) influx alters the kinetics and amplitude of the global Ca(2+) response to glucose in pancreatic islets and significantly reduces insulin release in both sexes. The progression of diabetes in males is aggravated by a selective loss of β-cell mass, while a stronger basal insulin release alleviates the diabetes symptoms in most α(2)δ-1(−/−) female mice. Together, these findings demonstrate that the loss of the Ca(2+) channel α(2)δ-1 subunit function increases the susceptibility for developing diabetes in a sex-dependent manner.